ON THE DETOUR AND VERTEX DETOUR HULL NUMBERS OF A GRAPH - Santhakumaran, A. P.; Chandran, S. V. Ullas (Journal of the Indonesian Mathematical Society, 2014)
Abstract PDFDOI :Â http://dx.doi.org/10.22342/jims.20.1.175.1-9